RESEARCH OF INFLUENCE OF LIQUID ALUMINUM ON RESISTANCE OF THE STEEL AND CAST-IRON TOOL - S. S. Zhizhchenko; I. A. Shpareva; M. A. Turchanin; P. G. Agraval (Литьë и металлургия, 2013)
The study of the interaction of steel and cast iron with aluminum was performed by immersion, and isothermal holding. By optical and electron microscopy, the microstructure of the reaction zone was investigated. The partial enthalpy of dissolution of iron, steel and cast iron in liquid aluminum has been investigated by high-temperature calorimetry at 1773 K. X-ray analysis and microhardness measurements was used to study the phase composition of the reaction zone. The thermodynamic descriptions of the system Al–Fe and Al–C–Fe are performed within the CALPHAD-method.